Tissue Necrosis in Equine Associated with use of Phenylbutazone - Freitas, Marina Sereno de; Medeiros, Bianca Pachiel; Pessoa, Josiane Magaton Nunes; Gonçalo, Vinícius Vasconcellos; Silva, Andreza Amaral; Botteon, Paulo de Tarso Landgraf (Acta Scientiae Veterinariae, 2022)
Background: Wounds that occur with tissue necrosis and that result from the application of medications through the most diverse accesses are described as drug skin medical embolism or Nicholas syndrome in human medicine, with wide description. In veterinary medicine, this subject has not yet been described extensively and specifically in veterinary medicine, especially regarding to wounds that occurred after the application of non-intravenous medications in horses, even though these lesions are recurrent in the clinical routine. This report aims to describe a case of skin necrosis in a horse, due to phenylbutazone infection. Case: A 7 year-old Mangalarga Marchador horse, weighing 400 kg, was admitted to the Veterinary Hospital for Large Animals of the Universiade Federal Rural do Rio de Janeiro (UFRRJ), with a history of phenylbutazone injection to the left side of the neck. The animal had an extensive wound on the neck and face on the left side and was characterized by the presence of cold and devitalized skin, with a hardened and parched appearance and that easily detached. During the anamnesis, a single administration of 10 mL of a non-steroidal anti-inflammatory drug based on phenylbutazone was reported intramuscularly for about 10 days to control the pain resulting from the claudication present for 14 days. The medication was administered in the region of the lateral border of the neck, on the left side. After drug administration, the animal presented an increase in volume at the application site. After 24 h, the lesion spread from the inoculation region, extending to the head and chest of the animal. During debridement, it was found that the lesion did not reach the underlying muscle tissue. In addition to the wound, the animal had upper eyelid palsy, lower lip, and auricular ptosis. Treatment with surgical debridement of devitalized tissue, topical application of ozonated sunflower oil, ketanserin, and a free skin graft was instituted. During hospitalization, the animal had a corneal ulcer in the left eye with an unfavorable prognosis due to paralysis of the upper eyelid, with enucleation of the affected eyeball. The animal was under veterinary care for 180 days and was discharged when his wound was already in an advanced stage of healing. Discussion: The history of the application of phenylbutazone intramuscularly and the location and characteristics of the lesion presented by the patient in the present report suggest that this animal presented aseptic tissue necrosis resulting from the administration of non-steroidal anti-inflammatory drugs, phenylbutazone. Although aseptic tissue necrosis, better known as Nicolau’s syndrome or drug embolism cutis, is widely characterized and described in this species, there are studies in the literature that reproduce the syndrome in pigs and rabbits. Phenylbutazone was able to cause arterial damage, mainly in the tunica intima of the artery in which the medication was administered, with perivascular inflammatory infiltrate and subsequent skin necrosis at the site of administration. In addition to the skin lesion, the animal started to show signs compatible with the left facial nerve lesion, evidenced by the immobility of the upper eyelid and labial and ear ptosis. This resulted in corneal ulceration and subsequent enucleation. The animal also developed chewing difficulty in the first months of hospitalization. This dysfunction may be due to a lesion of the mandibular nerve, responsible for innervating the masticatory muscles and the oral mucosa. However, the animal showed improvement in this aspect, no longer showing this condition after 90 days of hospitalization. The treatment used was successful in healing the wound. Keywords: wound, tissue necrosis, iatrogenic injury, Nicolau Syndrome, treatment, horse. Título: Necrose tissular em equino associada ao uso de fenilbutazona. Descritores: ferida, necrose tecidual, iatrogenia medicamentosa, síndrome de Nicolau, tratamento, cavalo.